Surgical colic caused by fibrous bands and adhesions in absence of previous abdominal surgery: 9 cases (2012–2019). (10th June 2021) - Giusto, G.; Cerullo, A.; Gandini, M.
Summary: Background: Intestinal pathologies caused by adhesions or fibrous bands in the absence of previous abdominal surgery have been reported in humans but rarely in horses. Objectives: To describe the clinical and surgical features of acute colic in horses caused by adhesions or fibrous bands in the absence of previous abdominal surgery. Study design: Retrospective case series. Methods: Records of horses that underwent exploratory laparotomy at the University of Turin VTH between 2012 and 2019 were reviewed. Clinical and surgical features of cases diagnosed with adhesions or fibrous bands as the primary cause of colic were retrieved, excluding those that had a history of previous abdominal surgery, either for gastrointestinal or urogenital problems. Results: Nine out of 293 horses which underwent exploratory laparotomy between 2012 and 2019 met the inclusion criteria for the study. In three cases, the adhesion involved the omentum (and the caecal apex, mesojejunum or mesocolon). In one case, a fibrous band 3–4 cm long running across the mesojejunum parallel to the small intestine strangled a loop of small intestine. In the remaining cases, the adhesion involved the left colon. Of these, two were geldings and the adhesion involved the internal inguinal ring region. Both had funiculitis after castration. The others were mares, and in one of them the adhesion was at the level of a small hernia in the left lateral abdominal wall. Main limitations: Small number of cases. Conclusions: This is the first case series of surgical colic caused by adhesions in a virgin abdomen. In horses, abdominal adhesions in the absence of previous abdominal trauma may be a cause of colic. Parturition, colon displacement and castration may be predisposing factors for the formation of intra‐abdominal adhesions.